Race and Ancestry in the Age of Inclusion: Technique and Meaning in Post-Genomic Science. (December 2014) - Shim, Janet K.; Ackerman, Sara L.; Darling, Katherine Weatherford; Hiatt, Robert A.; Lee, Sandra Soo-Jin
This article examines how race and ancestry are taken up in gene-environment interaction (GEI) research on complex diseases such as heart disease, diabetes, and cancer. Using 54 in-depth interviews of 33 scientists and over 200 hours of observation at scientific conferences, we explore how GEI researchers use and interpret race, ethnicity, and ancestry in their work. We find that the use of self-identified race and ethnicity (SIRE) exists alongside ancestry informative markers (AIMs) to ascertain genetic ancestry. Our participants assess the utility of these two techniques in relative terms, downplaying the accuracy and value of SIRE compared to the precision and necessity of AIMs. In doing so, we argue that post-genomic scientists seeking to understand the interactions of genetic and environmental disease determinants actually undermine their ability to do so by valorizing precise characterizations of individuals' genetic ancestry over measurement of the social processes and relations that differentiate social groups.